2009
DOI: 10.1080/10401330903228513
|View full text |Cite
|
Sign up to set email alerts
|

Correctional Health Curriculum Enhancement Through Focus Groups

Abstract: The successful provision of health care in correctional settings requires specialized knowledge, skills, and awareness not typically available in other health care training settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…21 Although few geriatrics training programs exist for staff other than health care providers within correctional systems, 22 both correctional health care providers and correctional staff have requested training in geriatrics. 23 …”
Section: Resultsmentioning
confidence: 99%
“…21 Although few geriatrics training programs exist for staff other than health care providers within correctional systems, 22 both correctional health care providers and correctional staff have requested training in geriatrics. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Programs also aim to impart these specific skills and attitudes to inform a trainee's future primary care practice. 18 One limitation of our study is that we may not have identified all programs involved in correctional health training. In future reviews, more varied keyword phrases and searches could be used to identify additional programs.…”
Section: Discussionmentioning
confidence: 98%
“…18 There are special knowledge, skills, and attitudes that are required to prepare competent correctional health care professionals. Programs focus on teaching students skills to treat medical conditions prevalent among inmates, with attention to health care delivery in the unique correctional setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations